2007
DOI: 10.1007/s11302-007-9079-6
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine reduces apoptosis and inflammation associated with restoration of function in rats with acute spinal cord injury

Abstract: Spinal cord injury results in progressive waves of secondary injuries, cascades of noxious pathological mechanisms that substantially exacerbate the primary injury and the resultant permanent functional deficits. Secondary injuries are associated with inflammation, excessive cytokine release, and cell apoptosis. The purine nucleoside guanosine has significant trophic effects and is neuroprotective, antiapoptotic in vitro, and stimulates nerve regeneration. Therefore, we determined whether systemic administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Guanosine has been studied in a variety of experimental neuropathological contexts, including brain trauma [49], glucose deprivation, [29] pathological events involved in spinal cord injury [50], and seizures [14,27]; however, the precise mechanism of guanosine's neuroprotective effects is not completely understood. Some data support the existence of specific receptor-like binding sites for guanosine [17,51,52], and data also indicate that the extracellular effects of guanosine may involve the activation of intracellular signaling pathways, including the involvement of G proteins, MAPK, PI3K, and HO-1 [17,30,51,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Guanosine has been studied in a variety of experimental neuropathological contexts, including brain trauma [49], glucose deprivation, [29] pathological events involved in spinal cord injury [50], and seizures [14,27]; however, the precise mechanism of guanosine's neuroprotective effects is not completely understood. Some data support the existence of specific receptor-like binding sites for guanosine [17,51,52], and data also indicate that the extracellular effects of guanosine may involve the activation of intracellular signaling pathways, including the involvement of G proteins, MAPK, PI3K, and HO-1 [17,30,51,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…1), it is not surprising that this nucleoside was shown to be neuroprotective both in vitro and in vivo against a plethora of different insults, including excitotoxins [95,96], apoptosis induced by staurosporine [86], stress-induced oxidative damage [97], sepsis-induced cognitive impairment [98], hepatic encephalopathy [99], azide-induced oxidative damage [100], lipopolysaccharide (LPS)-induced inflammation [94], ischemic damage [63,101,102], toxicity induced by amyloid β peptide (Aβ) [91,103] as well as 1-methyl-4-phenylpyridinium (MPP + ) and 6-hydroxydopamine (6-OHDA) [36,[104][105][106], and spinal cord injury (SCI) [107,108]. Based on these studies, the modulation of the purinergic system has emerged as a therapeutic approach for the treatment of various neurological conditions, and guanosine in particular may be a therapeutic target for several of these neuropathologies.…”
Section: The Effects Of Guanosine In Cns Neuropathologiesmentioning
confidence: 99%
“…Taking into account that, in addition to its wellestablished neuroprotective activities, guanosine also stimulates regenerative processes in the CNS [15], various studies sought to investigate the potential of this nucleoside as a therapeutic intervention for the treatment of SCI. Within this scenario, one study has demonstrated that repeated systemic administration of guanosine for a period of 2 weeks following SCI in rats (beginning 4 h post-injury) results in an improvement of sensory and motor function as well as a reduction in inflammation and apoptotic cell death, an effect probably attributable to its neuroprotective properties [107]. Importantly, in support of the idea that guanosine also stimulates regenerative processes [15], it has been shown that this nucleoside is able to induce functional recovery even when administered 5 weeks after SCI, an effect that is accompanied by the activation of endogenous cells from the oligodendrocyte lineage and remyelination of the surviving nerve fibers [108,168].…”
Section: Protective Effects Of Guanosine In Neurodegenerative Diseasesmentioning
confidence: 99%
“…There is growing evidence to indicate that guanosine has a neuroprotective role in neurodegenerative processes due to anti-apoptotic, anti-inflamatory and neurotrophic effects, and also to its ability to prevent glutamate excitotoxicity by stimulating astrocytic glutamate uptake [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]55]. More importantly, it has already been shown that, in two different models of PD, the administration of guanosine can promote neuroprotection or, at least, reduce motor symptoms [24,26].…”
Section: Discussionmentioning
confidence: 99%